ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT MENJADI NASABAH ASURANSI SYARIAH TAKAFUL DALAM PROGRAM ASURANSI PENDIDIKAN ANAK - Indry Yani Rahayu; Erma Mega Cahyaningsih; M. Syakroni; Kustin Hartini (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRACTThe problem or purpose of this research is to find out and analyze factors that influence community interest in the Hibrida 8 Kelurahan Sidomulyo, Kecamatan Gading Cempaka, Kota Bengkulu to become a costomer in insurance Tafakul syariah Benggkulu city. This research is a type of field research with expos facto quantutative approach. Sources of data used in this study are primary data by collecting data using servey and questionnaires. Sampel on this study consisted of 60 families The analytical technique used to test the validity of the data is the pearson correlation, while the reliability test uses the cronbach alpha method and using factor anality with the bartleet test of sphericity method. From result the research shows that from 6 variables identified as public interest variables to sharia insurance, especially insurance for children’s education in bengkulu. From 6 variables studied (x1) product, (x2) promotion, (x3) economic, (x4) personal, (x5) social, (x6) psychology.Keywords : Influencing Factors, Costomers, Children’s Education Insurance Program